Working Capital Management of Auto Component Industry: A study on the working capital management and growth of the Indian auto-components industry (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Indian auto-components industry has experienced healthy growth over the last few years. Some of the factors attributable to this include: a buoyant end-user market, improved consumer sentiment and return of adequate liquidity in the financial system. The revival of the auto industry was initially driven by the fiscal stimulus programme of the government. Secondary data has been used for achieving the objectives of the study.